Adaptability in Swimming Pattern: How Propulsive Action Is Modified as a Function of Speed and Skill - Schnitzler, Christophe; Seifert, Ludovic; Button, Chris (Frontiers in Sports and Active Living, 2021)
The objectives of this study were to identify how spatio-temporal, kinetic, and kinematic parameters could (i) characterise swimmers’ adaptability to different swimming speeds and (ii) discriminate expertise level among swimmers. Twenty male participants grouped into (a) low-, (b) medium-, and (c) high-expertise levels swam at three different swim paces of 60%, 85% (20s), and 100% (10s) of their maximal speed in a swimming flume. We used three underwater video cameras to derive spatio-temporal parameters (stroke rate, stroke length, stroke index). Force sensors placed on the hands were used to compute intra- and inter-arm coordination (in conjunction with video data) and kinetic parameters (in both time and frequency domains). Parametric statistics examined speed and expertise effects. Results showed that some similarities were found across expertise levels to increase swim speed: stroke rate (SR), the percentage of time devoted to propulsion within a cycle, and the index of coordination (IdC) increased significantly. In contrast, the force impulse (I+) generated by the hand during propulsion remained constant. Only the high-expertise group showed modification in the spectral content of its force distribution at high stroke rate. Examination of spatio-temporal parameters showed that only high expertise swimmers exhibited higher values of both stroke length and stroke index, and that the low- and high-expertise groups exhibited similar IdC and even higher magnitude in I+. In conclusion, all swimmers exhibit adaptable behaviour to change swim pace when required. However, high-skilled swimming is characterized by broader functional adaptation in force parameters as a result of intra-limb coordination variability.